EPIDEMIC AND TEMPLE ENTRY: HISTORY OF PALLURUTHY PULAVANIBHAM - Manjusha S M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Palluruthy Pulavanibham is a historic trade festival held annually at the Azhakiyakavu Temple in Palluruthy, Kerala, on the last Thursday of the Malayalam month Dhanu. Its origins trace back to the late 1700s when a smallpox epidemic afflicted the Pulaya community residing near the temple. Seeking relief, they were advised to worship the temple's deity but faced entry restrictions due to prevailing caste prohibitions. Upon their appeal, the King of Cochin permitted their entry through the temple's northern gate on this specific day each year. This event evolved into a marketplace where the Pulaya people sold handcrafted goods to fund their pilgrimage. Over time, Pulavanibham has transformed into a vibrant fair, attracting merchants and visitors from various regions, symbolizing social inclusion and cultural heritage.